The Philippines : Trade Facilitation Challenges for Women Traders and Customs Brokers - Warren, Heidi Stensland,Yang,Aileen Duong,Galang,Roberto Martin Nolan,Ochieng,Zachary Ochola,Raziyeva,Mariyam (World Bank, Washington, DC, 2022)
The World Bank Group completed the trade and gender study in the Philippines to identify the specific challenges that men and women face in cross-border trade and determine where further reforms can be made. Over 2,000 traders and customs brokers were interviewed. The report provides a wealth of new data and includes a summary of key findings, as well as recommendations on how to address the main obstacles identified. This analysis can help governments better understand trade barriers and design policy that maximizes the benefits of trade for women, so that they can participate more fully in the economy.